Case Report: Amyloid-Producing Odontogenic Tumor With Pulmonary Metastasis in a Spinone Italiano—Proof of Malignant Potential - Blackford Winders, Callie; Bell, Cynthia M.; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2020)
A 1 year-old male Spinone Italiano dog was treated for an amyloid producing odontogenic tumor on the right maxilla with a cytoreductive surgery followed by a definitive radiation protocol. Six years later the dog presented for a new mass on the rostral mandible as well as a new lung nodule without recurrence of the original maxillary tumor. Both the mandibular mass and the lung nodule were histologically confirmed to be amyloid producing odontogenic tumor based on the appearance of sheets and cords of odontogenic epithelium disrupted by amorphous extracellular amyloid. The primary difference between the pathology of the original APOT, secondary APOT, and metastatic APOT was a higher mitotic rate in the initial oral tumor (25 mitotic figures per 10 high power fields) and metastatic lung tumor (40 per 10 hpf) versus the second oral tumor (0 per 10 hpf). Thus, with protracted time from initial treatment, there isThis case illustrates a metastatic potential for amyloid producing odontogenic tumor in dogs and asynchronous occurrence of multiple APOTs in the oral cavity.